Intramolecular Oxidative Heck Cyclization: a Novel Pathwayto Cyclopentenones - Nguyen, Thanh Vinh (CSIRO Publishing, 2008)
An efficient method for the preparation of cyclopentenones via palladiumcatalyzedHeck-type intramolecular cyclization may be employed to synthesizeframeworks for natural products and bioactive compounds.